Creativity myths: Prevalence and correlates of misconceptions on creativity. (November 2021) - Benedek, Mathias; Karstendiek, Martin; Ceh, Simon M.; Grabner, Roland H.; Krammer, Georg; Lebuda, Izabela; Silvia, Paul J.; Cotter, Katherine N.; Li, Yangping; Hu, Weiping; Martskvishvili, Khatuna; Kaufman, James C.
Abstract: Myths about creativity keep contributing to its mysterious aura despite our increasing scientific understanding of this complex phenomenon. This study examined the prevalence of known creativity myths across six countries from diverse cultural backgrounds and explored why some people believe in them more than others. Results revealed persistent, wide-spread biases in the public conception of creativity, such as attributing creative achievements to spontaneity and chance rather than persistence and expertise. Firmer belief in creativity myths was related to lower education, stronger reliance on undependable sources, and personality traits reflecting the willingness to accept questionable notions and to rely on opinions of others. The findings highlight the need for better communication of evidence-based knowledge to enable more effective support for creativity.